University legal learning spaces effectiveness in developing employability skills of future Law graduates - Turner, Jason James; Amirnuddin, Puteri Sofia; Iqbal Singh, Harmahinder Singh (Universiti Utara Malaysia Press, 2019)
Purpose - The objective of this study was to examine the role of legal learning space in a Malaysian university and how this space impacts on law students' preparation for the employment market. This study comes in response to the issue of inexperienced graduates, who lack appropriate employability skills for the world of work, commonly referred to as the ‘graduate skills gap.